101 design methods : a structured approach for driving innovation in your organization - Kumar, Vijay (Wiley, 2012)
A guide for successful innovation planning. It is suitable for strategists, managers, designers, and researchers who undertake the challenge of innovation, despite a lack of established procedures and a high risk of failure.
Keywords: Technological innovations; Organizational change; New products; Product design; organisaatiomuutokset; teknologinen kehitys; innovaatiot; palvelut; kehitysstrategiat; palvelustrategiat; strateginen suunnittelu; menetelmät; suunnittelumenetelmät; organisaatiot; luovuus; tuotekehitys